Investigating the Richness of Archeological Data of Megalithic Culture in Iyang-Ijen Plateau to Develop Local History Learning Material - Kayan Swastika (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2021)
This research focused on attempting to solve issues regarding the distribution and typology of megalithic culture traces in the plateau of Iyang-Ijen along with its chronology. This study aimed to discover the richness of archeological data within the area to develop local history learning material that contextual and valuable, both in higher education or in schools. The study was performed using historical method with historical archeology approach. The results and discussion indicate that the width of cultural trails of megalithic culture in Iyang-Ijen plateau covered 82 villages and 34 sub-districts. The exact amount of archeological remains are 1.767 items. The typology itself are 21 types. The timeline of appearance and development of megalithic culture within Iyang-Ijen Plateau occurred since V – XV AD and lasted about XVIII – XIX AD.